Does the student's perspective on multimodal literacy influence their behavioural intention to use collaborative computer-based learning? - Oluwajana, Dokun; Adeshola, Ibrahim (Springer, 2021)
The support for the use of Computer-Supported Collaborative Learning is a sign of contributions and support for in-class and out-of-class learning. This study investigates the perspective of student's digital multi-modal literacy on student's behavioral intention to use a CSCL. We proposed a theoretical model that examines student perspectives on the integration of digital multi-modal literacy in the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The study empirically examined and validated the proposed theoretical model based on a digital multi-modal computer-supported collaborative learning adoption. The data were analyzed with a partial least square, structural equation modeling (PLS-SEM) statistical approach. Results suggest that student's perspective on multi-modal literacy has a positive and significant impact on the behavioral intention to use. Furthermore, all the UTAUT factors have a strong and significant impact on the behavioral intention to support the use of digital multi-modal computer-supported collaborative learning. Therefore, student's perspective on multi-modal literacy contributes towards their behavioural intention to use collaborative computer-based learning. To further improve collaboration and communication based on the use of CSCL to support students learning environment.
Keywords: Multi-modal literacy; Computer-supported collaborative learning; Learner engagement; Digital platforms; Generational cohort